The daily minimum leaf turgor pressure can represent the water status of apple trees under drip irrigation - Chen, Ruixia; Xu, Quanyue; Wan, Junliang; Jiang, Nan; Ma, Juanjuan; Zheng, Lijian (Frontiers in Plant Science, 2024)
IntroductionAccurate diagnosis of the water status of fruit trees is a prerequisite for precise irrigation. Measurement of leaf turgor pressure provides a means to explore the water utilization mechanisms of fruit trees and their responses to water stress. However, there are few studies on the use of daily minimum leaf turgor pressure (Ppmax) to indicate water information in apple tree.MethodsWe monitored Ppmax, stem flow rate (Vstem), leaf water potential, soil water, and the main meteorological factors under two drip irrigation levels (fully irrigated and under-irrigated) to elucidate the temporal dynamics of the daily leaf turgor minimum of apple trees and diagnose the water status of fruit trees.ResultsThe results showed that soil water deficiency could reduce leaf turgor pressure and increase Ppmax. In both years, the signal intensity and sensitivity of Ppmax were better than those of Vstem, and the sensitivity was 3.31 and 2.94 times of Vstem, respectively. Compared to Ppmax, Vstem had a higher correlation with meteorological factors and was more affected by meteorological conditions, independent of irrigation treatment. Ppmax was significantly negatively correlated with soil and leaf water potential, and its correlation coefficient was 2.58–4.89 times higher than that between Vstem and both.DiscussionThese results not only enhance our understanding of the water regulation strategies employed by apple trees under drought conditions but also provide a theoretical foundation for developing efficient water-saving practices and precision irrigation strategies for fruit trees.